Factors regulating lignocellulolytic microbes, their degrading enzymes, and heterotrophic respiration in oil palm cultivated peatlands - Hadi, Muhammad Nurul; Pulunggono, Heru Bagus; Indriyati, Lilik Tri; Widiastuti, Happy; Zulfajrin, Moh (Journal of Degraded and Mining Lands Management, 2024)
Even though their role in mediating tropical peat decomposition and GHG emissions had been widely recognized, information concerning lignocellulolytic microbes, their degrading enzyme ability, and interconnection with soil physicochemical properties and peat heterotrophic respiration on mature oil palm plantation/OPP block level were rudimentary. This study evaluated the effect of sampling depth (0-30, 30-60, and 60-90 cm), OPP management zone (fertilization circle/FTC, frond stack/FRS, and harvesting path/HVP), and peat physicochemical properties on the lignocellulolytic bacteria and fungi, their degrading enzymes activities and peat heterotrophic respiration/Rh using principal component analysis/PCA, multiple linear regression/MLR, and generalized linear mixed effect models/GLMM. This study found that the soil microbiological and physicochemical properties varied widely. Dominant lignocellulolytic bacterial population and their cellulase enzyme activity were higher than fungi, regardless of sampling depth and management zone. PCA and GLMM analyses showed the significant importance of sampling depth and management zone in governing lignocellulolytic microbial population, their enzyme activities, and Rh. Microbial population and cellulase activity were also remarkably affected by the interaction of all studied factors. Peat chemical properties (pH and total Mn) controlled the natural variance of lignocellulolytic microbes and their enzymes, whereas total K regulate Rh. This study suggested that the research on microbiological-related GHG mitigation in OPP should be focused on managing the fungal population and cellulase enzyme activity at the peat surface (0-30 cm) and fertilization circle.